Contemporary cryptic sexuality in Trypanosoma cruzi (2012)
Clonal propagation is considered to be the predominant mode of reproduction among many parasitic protozoa. However, this assumption may overlook unorthodox, infrequent or cryptic sexuality. Trypanosoma cruzi , which causes Chagas disease, is known to undergo non?Mendelian genetic exchange in the laboratory. In the field, evidence of extant genetic exchange is limited. In this study, we undertook intensive sampling of T. cruzi Discrete Typing Unit I in endemic eastern Colombia. Using Fluorescence?activated cell sorting, we generated 269 biological clones from 67 strains. Each clone was genotyped across 24 microsatellite loci. Subsequently, 100 representative clones were typed using 10 mitochondrial sequence targets (3.76?Kbp total). Clonal diversity among humans, reservoir hosts and vectors suggested complex patterns of superinfection and/or coinfection in oral and vector?borne Chagas disease cases. Clonal diversity between mother and foetus in a congenital case demonstrates that domestic TcI genotypes are infective in utero . Importantly, gross incongruence between nuclear and mitochondrial markers is strong evidence for widespread genetic exchange throughout the data set. Furthermore, a confirmed mosaic maxicircle sequence suggests intermolecular recombination between individuals as a further mechanism of genetic reassortment. Finally, robust dating based on mitochondrial DNA indicates that the emergence of a widespread domestic TcI clade that we now name TcIDOM (formerly TcIa/VENDom) occurred 23?000?±?12?000?years ago and was followed by population expansion, broadly corresponding with the earliest human migration into the Americas.